Recent Advances in Denitrogenative Reactions of Pyridotriazoles - Filippov, Ilya P.; Titov, Gleb D.; Rostovskii, Nikolai V. (Synthesis, 2020)
Diazo compounds display versatile reactivity and therefore are widely used in organic synthesis. Diazo compounds bearing a 2-pyridyl or a related azine moiety on the diazo carbon exist in the form of fused 1,2,3-triazoles. In this short review, we summarize the recent advances in denitrogenative reactions of [1,2,3]triazolo[1,5-a]pyridines (‘pyridotriazoles’) and related fused 1,2,3-triazoles. Over the past decade, there has been a surge of activity in this field, with novel denitrogenative reactions of pyridotriazoles induced by metal compounds, light, and Brønsted and Lewis acids having been devised. As a result, heterocyclic compounds and functionalized α-picolines as well as bioactive molecules have been synthesized. In the review, emphasis is also placed on the mechanisms of the new reactions.1 Introduction2 Ring-Chain Isomerization of Pyridotriazoles3 Metal-Catalyzed Reactions3.1 Rh(II) Catalysis3.2 Rh(III) Catalysis3.3 Cu Catalysis3.4 Pd Catalysis3.5 Catalysis by Other Metals4 Metal-Free Reactions5 Conclusion
Keywords: pyridotriazoles; 1,2,3-triazoles; diazo compounds; carbenes; catalysis; nitrogen heterocycles; α-picolines